Noise thermometry applied to thermoelectric measurements in InAs nanowires. (6th September 2016) - Tikhonov, E S; Shovkun, D V; Ercolani, D; Rossella, F; Rocci, M; Sorba, L; Roddaro, S; Khrapai, V S
Abstract: We apply noise thermometry to characterize charge and thermoelectric transport in single InAs nanowires (NWs) at a bath temperature of 4.2 K. Shot noise measurements identify elastic diffusive transport in our NWs with negligible electron–phonon interaction. This enables us to set up a measurement of the diffusion thermopower. Unlike previous approaches, we make use of a primary electronic noise thermometry to calibrate a thermal bias across the NW. In particular, this enables us to apply a contact heating scheme, which is much more efficient in creating the thermal bias as compared to conventional substrate heating. The measured thermoelectric Seebeck coefficient exhibits strong mesoscopic fluctuations in dependence on the back-gate voltage that is used to tune the NW carrier density. We analyze the transport and thermoelectric data in terms of an approximate Mott's thermopower relation and evaluate a gate-voltage to the Fermi energy conversion factor.